Communicating the User Experience: A Practical Guide for Creating Useful UX Documentation - Caddick, Richard; Cable, Steve (John Wiley & Sons, Incorporated, 2011)
A clear and focused guide to creating useful user experience documentation As web sites and applications become richer and more complex, the user experience (UX) becomes critical to their success. This indispensible and full-color book provides practical guidance on this growing field and shares valuable UX advice that you can put into practice immediately on your own projects. The authors examine why UX is gaining so much interest from web designers, graduates, and career changers and looks at the new UX tools and ideas that can help you do your job better. In addition, you'll benefit from the unique insight the authors provide from their experiences of working with some of the world's best-known companies, learning how to take ideas from business requirements, user research, and documentation to create and develop your UX vision. Explains how to create documentation that clearly communicates the vision for the UX design and the blueprint for how it's going to be developed Provides practical guidance that you can put to work right away on their own projects Looks at the new UX tools and ideas that are born every day, aimed at helping you do your job better and more efficiently Covers a variety of topics including user journeys, task models, funnel diagrams, content audits, sitemaps, wireframes, interactive prototypes, and more Communicating the User Experience is an ideal resource for getting started with creating UX documentation.